The Subdominant Tritone in Film and Television Music - Osborn, Brad (Current Musicology, 2021)
Tritones sounding over subdominant harmony, either as suspensions, accented passing tones, or incomplete neighbors, constitute a class of sonorities regularly heard in film and television music. I collectively refer to these phenomena as “subdominant tritones” (SdTT), and theorize a link between the SdTT and emotions it engenders. The article presents close visual/musical analysis of selected SdTT-tinged passages in feature films that animate various heightened emotional states, including longing, nostalgia, relief, and melancholy. [Please note: This article contains embedded video files. These files cannot be played on all PDF readers. Current Musicology recommends Foxit PDF Reader, Adobe Acrobat, or any other PDF reader capable of reading "enriched" media.]